Growth of corporate investment: an attempt at projection for 1999-2000 - Satyanarayana, R.; Bose, Sanjoy (1999)
The behaviour of corporate investment provides insights into the business expectations about the performance of economy in general and the manufacturing sector in particular. Projections of capital investment in the private corporate sector provide important clues about investment intentions. The theories of investment do not provide much guidance in this regard. This paper attempts to project the likely growth of private corporate investment in India in 1999-2000. - Reproduced
Keywords: Financial markets